(untitled) (مجلة جامعة بابل للعلوم الانسانية, 2018)
Denial was and still is a way for a person to reject the real and painful reality that lies ahead. The images of denial and its pluralism in the theatrical structure have a role in clarifying the spatial and dialogical data and indications through the experiments and this is what makes the denial is achieved in all components of the theatrical test, according on the style and nature of the writer so this research consists of four chapters, the first chapter (the methodological framework) has the problem of the research that I have done with the following question:- What is denial? And what are their representations in theatrical text. The importance of the research was on the social and psychological reasons that explain and find out the solutions, and the aim of the research to recognize the denial and its representations in the theater text. the research was limited in time (2011) and place in Germany this chapter concluded with the definition of terms either Chapter II (theoretical framework), which consists of two sections specialized the first section of philosophical innovation, in terms of the second section devoted to the denial in the Western theater text, and concluded the chapter with the indicators that resulted from the theoretical framework and the chapter concluded with the indicators that resulted from the theoretical framework, and the third chapter has been specialized in the research procedures, which was represented in the statement of the research, the type of research, and research methodology, then analysis the sample of the research. The fourth chapter also included the results of the research as the following: 1-The basic images of denial and consists of direct and indirect positions within the text of the text and also through breaking the familiar and transformed into an unfamiliar that is embodied by the reader while reading the text 2-The denial contributes to rid the person of the tension and psychological and intellectual anxiety caused by the occurrence of the real reality in front of him as in the play (seven seconds in the Rab Nathiq) Finally, the conclusions, to finish the research list of sources and then the summary of the research in English.